2019
DOI: 10.2495/ws190211
|View full text |Cite
|
Sign up to set email alerts
|

Urban Wastewater Treatment Through a System of Green Filters in the Montañita Commune, Santa Elena, Ecuador

Abstract: In land application, soil is used as a natural filter to remove pollution from urban wastewater. The soil also has two other functions, first of all it's the receiving medium of wastewater and secondly it works as an active agent because physical, chemical and biological reactions are made in the soil-water-crops ecosystem. This non-conventional treatment is effective at removing pollutants such as suspended solids, organic matter, nitrogen, phosphorus and microorganism form effluent streams. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…However, since the creation of JAAPMAN, the success factors have been community participation based on ancestral knowledge [62], the interaction between the academy and the community, and the ability to make alliances reflected in technical cooperation projects with national and international organizations [63,67]. In addition, the key factors are projects with practices based on sustainability, such as treating wastewater through green filters and promoting reforestation, thus, expanding the social responsibility of supplying water to the population by attending to wastewater and integrating it into the water cycle (Figures 2-4) [72]. Ultimately, the sum of all these elements allows the community in its specific territory to participate in solutions and have resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the creation of JAAPMAN, the success factors have been community participation based on ancestral knowledge [62], the interaction between the academy and the community, and the ability to make alliances reflected in technical cooperation projects with national and international organizations [63,67]. In addition, the key factors are projects with practices based on sustainability, such as treating wastewater through green filters and promoting reforestation, thus, expanding the social responsibility of supplying water to the population by attending to wastewater and integrating it into the water cycle (Figures 2-4) [72]. Ultimately, the sum of all these elements allows the community in its specific territory to participate in solutions and have resilience.…”
Section: Discussionmentioning
confidence: 99%
“…The assistance of academia has promoted the protection of the aquifer, prohibited the exploitation of construction material, and implemented reforestation campaigns in the area under study [62]. In 2017, CIPAT began community service projects to monitor the geometry of the aquifer, the water quality, and the wastewater treatment with the application of green filters to maintain and ensure water sustainability ( Figure 4) [72]. The actions by public institutions and academia have shown that the efforts of management policies to counteract the effects of scarcity and the high demand for water in groundwater basins such as the Manglaralto basin have not been enough.…”
Section: Case Study: Manglaraltomentioning
confidence: 99%
“…The Manglaralto parish has excellent geological diversity that promotes tourist activity in the sector and its conservation of geosites and sustainable development in various areas, such as social, economic, environmental, and cultural [25,26]. Its resilience is reflected in the management of drinking water through the coastal aquifer and the supply to its six communes, the conservation of geosites and increase of its tourist resource, the management of its wastewater through green filters, among other projects focused mainly on the progress and advancement of the community [27][28][29].…”
Section: Site Descriptionmentioning
confidence: 99%
“…On the other hand, the issue of water and its management has recently been treated as an object of greater interest by many government researchers thanks to community participation, accompanied by ancestral knowledge, which have been key factors in solving problems regarding obtaining and distributing water, ensuring that the residents develop techniques to recharge the aquifer [18]. Within this participation, there are other significant parties involved, such as the International Atomic Energy Organization (IAEA) and the ESPOL Polytechnic University, which together with the community have managed to meet the growing water demand, rescuing ancestral knowledge by implementing tapes (artisanal dykes), addressing the overexploitation of the aquifer and empowering communities in water management [42]. However, in the geographical environment, problems remain due to tourism growth and climate change.…”
Section: Introductionmentioning
confidence: 99%